Penggunaan Video Animasi Bahasa Arab Fawwaz dan Nuroh dalam Meningkatkan Keterampilan Mendengar Peserta Didik MA Plus Nurul Islam Sekarbela - Lia Dianti; Dedi Riyan Rizaldi; Muhammad Fahrurrozi; Ririn Novitasari; Nilwan; Ziadatul Fatimah (Lembaga Einstein College (LEC), 2024)
Meaningful learning for students is a challenge for every teacher in every learning process. To create meaningful learning conditions, it is necessary to use various approaches that are adjusted to the characteristics of the material and students. The purpose of this study was to determine the role of using Arabic animation videos of Fawwaz and Nuroh in improving students' listening skills at MA Plus Nurul Islam Sekarbela. This study uses a type of classroom action research with a qualitative approach that goes through two learning cycles. The subjects in this study were grade XI students majoring in Religion at MA Plus Nurul Islam Sekarbela. The data in this study were obtained through observation, interview, and documentation methods. All data obtained were analyzed descriptively. The results of this study showed that the use of Arabic animation videos of Fawwaz and Nuroh can be proven to improve students' listening skills at MA Plus Nurul Islam Sekarbela